2017
DOI: 10.1007/s10653-017-9926-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative potential (OP) and mineralogy of iron ore particulate matter at the Gol-E-Gohar Mining and Industrial Facility (Iran)

Abstract: Concentrations of total suspended particulate matter, particulate matter with aerodynamic diameter <2.5 μm (PM2.5), particulate matter <10 μm (PM10), and fallout dust were measured at the Iranian Gol-E-Gohar Mining and Industrial Facility. Samples were characterized in terms of mineralogy, morphology, and oxidative potential. Results show that indoor samples exceeded the 24-h PM2.5 and PM10 mass concentration limits (35 and 150 μg m−3, respectively) set by the US National Ambient Air Quality Standards. Calcite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Since the SOM content of the investigated soils is very low, probably these PTEs could be associated with sulfides rather than to SOM. In fact, previous mineralogical studies revealed the presence of sulfide minerals, especially pyrite, chalcopyrite, pyrrhotite, pentlandite, and sphalerite in GEG iron ore (Nabatian et al 2015; Soltani et al 2017). …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the SOM content of the investigated soils is very low, probably these PTEs could be associated with sulfides rather than to SOM. In fact, previous mineralogical studies revealed the presence of sulfide minerals, especially pyrite, chalcopyrite, pyrrhotite, pentlandite, and sphalerite in GEG iron ore (Nabatian et al 2015; Soltani et al 2017). …”
Section: Resultsmentioning
confidence: 97%
“…Fallout dust can disperse over a wide area and may negatively affect the soil and plant in the area surrounding the facility. Mineralogical studies of particulate matter generated by grinding of iron ore indicated that dominant minerals include magnetite, hematite, kaolinite, talc, tremolite, calcite, albite, pyrite, and actinolite and minor amounts of quartz, hematite, dioptase, biotite, sphalerite, albite, chalcopyrite, nimite, magnesiohornblende, and muscovite (Soltani et al 2017). The mineralogical study of 15 representative soil samples proved the presence of primary minerals such as crystalline Fe-oxide (magnetite and hematite) and ferromagnesian minerals (biotite, ferroactinolite, chlorite, antigorite, talc, and clinochlor).…”
Section: Resultsmentioning
confidence: 99%
“…Dust is the most abundant aerosol type globally on a mass basis and affects climate, the water cycle, public health and welfare, and vegetation (Bollen et al, 2010; Manninen et al, 2013; Gibson, 2015; Matyssek et al, 2015; Madala et al, 2016; Carugno et al, 2016; Morelli et al, 2016; Raspanti et al, 2016; Youn et al, 2016; Soltani et al, 2017). Large deserts in the Middle East, such as those in Saudi Arabia, Iraq, and Syria, are major sources of dust where in recent years dust storm frequency and intensity has increased (Alam et al, 2014a; Boloorani et al, 2014; Jish Prakash et al, 2015; Shalaby et al, 2015; Gharibzadeh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nasal PM0.1 may also enter the brain directly via the olfactory bulb [ 82 ]. According to some authors, metal-based PM0.1 promotes DNA damage via oxidative stress, epigenetic alterations with consequences on gene expression [ 83 , 84 , 85 ], and even neurological disorders such as Alzheimer’s and Parkinson’s diseases [ 80 , 81 ].…”
Section: Airborne Particulate Matter (Pm) and Characteristics And Eff...mentioning
confidence: 99%